Вплив комплексного модифікатора на властивості периклазовуглецевих матеріалів із вмістом 15 – 20 % графіту - Семченко, Галина Дмитрівна; Повшук, В. В.; Борисенко, О. М.; Старолат, Олена Євгенівна (НТУ "ХПІ", 2014)
Influence complex sol–gel composition on the basis of hydrolyzing ethylsilicate with solution of chlorous nickel on physics–mechanical properties of the periclase–carbon refractories with maintenance of graphite in an amount 15 – 20 % is set in article. It is shown that at the use indicated sol-gel composition in an amount to 0,5 % porosity depends on the amount of graphite in a charge. At the increase of maintenance of composition porosity does not depend on the amount of graphite and does not exceed 23 % after burning at a temperature 1400 °С.
Influence of a complex modifier on properties of periclase carbon materials with maintenance 15 – 20 % graphite
Keywords: технологічні процеси; переробка сталі; техніко-економічні показники; sol–gel composition; chlorous nickel; periclase carbon refractories; rules